A Paradigm Shift in Law Enforcement Training in the Bahamas: Teacher-Centered to Learner-Centered. - Hunter-Johnson, Yvonne O.; James, Waynne B. (International Journal of Bahamian Studies, 2012)
This study focused on determining whether the learning preference of law enforcement officers in the Bahamas was either pedagogical (teacher-centered) or andragogical (student-centered). Law enforcement personnel in a Bahamian police department were administered the Student Orientation Questionnaire (SOQ) developed by Christian (1982). One hundred and sixty-eight individuals completed the SOQ. Chi square statistics were calculated on the variables of educational level and gender. The preferred learning orientation was primarily andragogical; those with higher education levels tended to have a higher andragogical orientation. There were no differences by gender. As a result of the findings, a three-step approach is proposed to transition the training environment from one that is teacher-centered to one that is learner-centered.